2013
DOI: 10.1371/journal.pone.0053744
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Recent Clinical Practice Guidelines on the Diagnosis, Assessment and Management of Hypertension

Abstract: BackgroundDespite the availability of clinical practice guidelines (CPGs), optimal hypertension control is not achieved in many parts of the world; one of the challenges is the volume of guidelines on this topic and their variable quality. To systematically review the quality, methodology, and consistency of recommendations of recently-developed national CPGs on the diagnosis, assessment and the management of hypertension.Methodology/Principal FindingsMEDLINE, EMBASE, guidelines' websites and Google were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 40 publications
(32 reference statements)
5
56
1
16
Order By: Relevance
“…The remaining three domains of scope and purpose, stakeholder involvement and clarity of presentation of the guidelines received high scores. These results are similar to a recent review of 11 reviews of CPGs of hypertension, which showed that the domains, rigour of development, applicability, and editorial independence scored consistently low across the CPGs 23 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The remaining three domains of scope and purpose, stakeholder involvement and clarity of presentation of the guidelines received high scores. These results are similar to a recent review of 11 reviews of CPGs of hypertension, which showed that the domains, rigour of development, applicability, and editorial independence scored consistently low across the CPGs 23 .…”
Section: Discussionsupporting
confidence: 88%
“…Discrepancies were resolved by discussion. The AGREE II instrument, which consists of 23 items, grouped into six quality domains: 1) Scope and purpose (items 1-3); 2) Stakeholder involvement (items 4-6); 3) Rigour of development (items 7-14); 4) Clarity of presentation (items 15-17); 5) Applicability (items 18-21) and 6) Editorial independence (items [22][23]. Each item was scored on a scale of 1-7, with 1 being strongly disagree, and 7 being strongly agree.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…There is sufficient evidence to support the critical need for health promotion and lifestyle modification interventions in addressing the high prevalence of hypertension in peri-urban areas in South Africa (Al-Ansary et al, 2013;Mungai-Singh, 2012). However, despite the higher tendency of urban black African dwellers to seek medical attention, research shows that adherence to behavioural interventions, such as dietary regimes, is in decline (King, Mainous, Carnemolla, & Everett, 2009;Marks, Murrary, Evans, & Estacio, 2011, van der Hoeven, Kruger, & Greef, 2012.…”
Section: Dietary Patterns In Peri-urban South African Settlementsmentioning
confidence: 99%
“…Consequently, implementing a more balanced and nutritious diet is essential for the prevention and mitigation of hypertension in South African communities (Appel et al, 1997). Despite the lack of improved national hypertension developed clinical practice guidelines (Al-Ansary et al, 2013), improved health-related outcomes for individuals with hypertension can still be achieved in these peri-urban communities. This article aims to highlight the utility of using psychological intervention techniques, namely motivational interviewing (MI) and cognitive behavioural therapy (CBT), to develop effective and culturally salient interventions to reduce the prevalence of hypertension in peri-urban areas of South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Hipertenzija predstavlja veliki medicinski problem današnjice sa prevalencom od 40 % među osobama starijim od 25 godina [1]. Pored velikog broja antihipertenziva i razvijene svijesti da kontrola hipertenzije dovodi do smanjenja komplikacija ove bolesti i troškova liječenja, procjenjuje se da prevalenca rezistentne hipertenzije iznosi između 20% i 30% [2].…”
Section: Uvodunclassified